1999
DOI: 10.1021/ja9836139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Charge and Intramolecular Structure on the Lipophilicity of Nitrophenols

Abstract: The lipophilicity of a series of phenolic compounds was studied in the 1,2-dichloroethane (1,2-DCE)/water system. Cyclic voltammetry at the ITIES was used to study the transfer characteristics of the charged species, and their partition coefficient was deduced from their formal transfer potential. For the neutral species, log P DCE values were measured by a two-phase pH-metric method. The results are compared to those previously obtained in octanol/water and by linear solvation energy relationships (LSER) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
3
51
0
Order By: Relevance
“…Further results qualitatively showed that the partitioning of ionic species can be related not only to the charge distribution around the molecule (electrostatic field) but also, and perhaps mainly, to the delocalisation (stabilisation) of the charge inside the molecule [148][149][150]. This is indeed in good agreement with the fact that short-range ion-solvent interactions (e.g.…”
Section: Pharmacokineticssupporting
confidence: 71%
“…Further results qualitatively showed that the partitioning of ionic species can be related not only to the charge distribution around the molecule (electrostatic field) but also, and perhaps mainly, to the delocalisation (stabilisation) of the charge inside the molecule [148][149][150]. This is indeed in good agreement with the fact that short-range ion-solvent interactions (e.g.…”
Section: Pharmacokineticssupporting
confidence: 71%
“…[1][2][3] The thermodynamics of a large number of organic and inorganic ions, such as the standard Gibbs energy of ion transfer, became feasible to evaluate by applying voltammetric programs at the ITIES in experiments performed with a four-electrode setup. 3,[5][6][7][8][9] Besides, a great number of electrochemical studies at ITIES have been devoted to the determination of the kinetics of ion transfer, [10][11][12][13][14][15][16] as well as to the elucidation of various electrode mechanisms involving the ion and/or electron transfers. [17][18][19][20][21][22] The standard Gibbs energy of ion transfer is an important physical parameter which can be deduced from the electrochemical experiments at ITIES, closely related to one of the most important characteristic of the compounds, that is, their lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, four electrode voltammetric measurements at the interface of two immiscible electrolyte solutions were the only tool for measuring the lipophilicity of single ions [1][2][3][4][5][6][7][8][9][10][11]. The weakness of this technique is mainly due to the presence of electrolytes in both the organic and the aqueous phases.…”
Section: Introductionmentioning
confidence: 99%